Vibrational dependence, temperature dependence, and prediction of line shape parameters for the H2O-N2 collision system. (September 2020) - Vispoel, Bastien; Cavalcanti, João H.; Paige, Evan T.; Gamache, Robert R.
Highlights: Half-width and line shifts for 94, 536 H2 O transitions broadened by N2 . Temperature dependence of γ and δ by the Gamache-Vispoel DPL model. Prediction routine for γ and δ and their temperature dependence. Nitrogen-broadened line list for H2 16 O, H2 18 O, and H2 17 O based on HITRAN2020. Abstract: In a recent work [JQSRT 228, 79(2019)], Vispoel et al. optimized the intermolecular potential used in the Modified Complex Robert-Bonamy (MCRB) formalism for the H2 O-N2 collision system. Calculations were made for a number of transitions in the rotation and ν2 bands. The needs of the spectroscopic and astrophysics communities include data for water vapor transitions that have multiple vibrational quanta exchanged. In this work, MCRB calculations were made for 0–4 vibrational quanta exchanged in the ν1, ν2, and ν3 bands for 13 temperatures from 200–3000 K; 7272 transitions for each band. From these data, the vibrational and temperature dependence of the half-width and line shift were determined. The temperature dependence was determined using the Gamache-Vispoel model [JQSRT 217, 440(2018)]. The data allowed the development of a routine that can predict the half-width, line shift, and their temperature dependence for transitions not yet studied. The prediction algorithm is based on theory [JQSRT, 83, 119(2004)] and yields line shape parameters with much smaller uncertainty than obtained by fitting with ad hoc polynomials or J" averaged values. A line file based on the 2020 update to the HITRAN2016 water vapor line file was created with N2 as the broadening species. These data are useful for combustion studies and as a first step to determining air-broadening for the HITRAN and GEISA databases. Graphical abstract: Image, graphical abstract